Vejrforholdene i Landbrugsaaret 1938—39. (Fra 1. Oktober 1938 til 30. September 1939). - Hansen, H. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1938—39. (Fra 1. Oktober 1938 til 30. September 1939).